Effects of Dietary Energy Levels on Rumen Fermentation, Microbial Diversity, and Feed Efficiency of Yaks (Bos grunniens) - Ahmad, Anum Ali; Yang, Chao; Zhang, Jianbo; Kalwar, Qudratullah; Liang, Zeyi; Li, Chen; Du, Mei; Yan, Ping; Long, Ruijun; Han, Jianlin; Ding, Xuezhi (Frontiers in Microbiology, 2020)
The microbial community of the Yak (Bos grunniens) rumen plays an important role in surviving the harsh Tibetan environment where seasonal dynamic changes in pasture cause nutrient supply imbalances, resulting in weight loss in yaks during the cold season. A better understanding of rumen microbiota under different feeding regimes is critical for exploiting the microbiota to enhance feed efficiency and growth performance. This study explored the impact of different dietary energy levels on feed efficiency, rumen fermentation, bacterial community, and abundance of volatile fatty acid (VFA) transporter transcripts in the rumen epithelium of yaks. Fifteen healthy castrated male yaks were divided into three groups and fed with low (YL), medium (YM), and high energy (YH) levels diet having different NEg of 5.5 MJ/kg, 6.2 MJ/kg and 6.9 MJ/kg, respectively. The increase in feed efficiency was recorded with an increase in dietary energy levels. The increase in dietary energy levels decreased the pH and increased the concentrations of acetate, propionate, butyrate, and valerate in yak rumens. The increase in the mRNA abundance of VFA transporter genes (MCT1, DRA, PAT1, and AE2) in the rumen epithelium of yaks was recorded as dietary energy level increased. High relative abundances of Firmicutes and Bacteroidetes was recorded with the increase in dietary energy levels. Significant population shifts at genus level were recorded among the three treatments. This study provides new insights into the dietary energy derived variations in rumen microbial community.